Practical aspects of compression therapy – Update 2016 - Protz, K.; Heyer, K. (Phlebologie, 2016)
Compression therapy is a complex form of therapy. It requires equally practical abilities and theoretical knowledge, as well as an understanding of available materials and the methods in question. All these mentioned aspects of today’s practical compression therapy show deficits.This article shows the current status of treatment of patients with venous leg ulcers in Germany. Based on this, strategies are described, which aim to improve the status of information of the patients, the expertise of the users and the further spread of modern and specialized materials.It is possible and appropriate to better the individual status of treatment of patients through further qualification of carers. This should include the proper usage of materials and methods.
Keywords: Compression therapy; venous leg ulcer; ulcerstocking systems; multi-component compression systems; adaptive compression bandages